A modelling approach to assess the long-term stability of a novel microbial/electrochemical system for the treatment of acid mine drainage. Issue 33 (22nd May 2018) - Brewster, Emma Thompson; Pozo, Guillermo; Batstone, Damien J.; Freguia, Stefano; Ledezma, Pablo
Abstract : Microbial electrochemical processes have potential to remediate acid mine drainage (AMD) wastewaters which are highly acidic and rich in sulfate and heavy metals, without the need for extensive chemical dosing. Abstract : Microbial electrochemical processes have potential to remediate acid mine drainage (AMD) wastewaters which are highly acidic and rich in sulfate and heavy metals, without the need for extensive chemical dosing. In this manuscript, a novel hybrid microbial/electrochemical remediation process which uses a 3-reactor system – a precipitation vessel, an electrochemical reactor and a microbial electrochemical reactor with a sulfate-reducing biocathode – was modelled. To evaluate the long-term operability of this system, a dynamic model for the fluxes of 140 different ionic species was developed and calibrated using laboratory-scale experimental data. The model identified that when the reactors are operating in the desired state, the coulombic efficiency of sulfate removal from AMD is high (91%). Modelling also identified that a periodic electrolyte purge is required to prevent the build-up of Cl − ions in the microbial electrochemical reactor. The model furthermore studied the fate of sulfate and carbon in the system. For sulfate, it was found that only 29% can be converted into elemental sulfur, with the rest complexating with metals in the precipitation vessel. Finally, the model shows that the flux of inorganic carbon under the current operational strategy is insufficient to maintain the autotrophic sulfate-reducing biomass. The modelling approach demonstrates that a change in system operational strategies plus close monitoring of overlooked ionic species (such as Cl − and HCO3 − ) are key towards the scaling-up of this technology.